Anthropocentric paradigm issues and the cognitive aspect of language universals - Auganbayeva, М.А.; Kurmanbekova, З.Р.; Issakova, А.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
The linguacultural values of the language allowing to reconstruct ideas and stereotypes manifested by a certain part of a language system. The definition of linguistic universals is given, which characterize languages or most of them. Accordingly, within the anthropocentric paradigm, the establishment of common and individual linguistic characteristics gives rise to the multifaceted field of modern linguistics, comprising a range of scientific directions. Universal language characteristics are regarded as informative material for linguacultural researches. They convey nationally determined interpretation of a word with other object through associations based on real or cultural codes. Basic and universal codes are distinguished among existing cultural codes in each culture. They are used to determine and express linguistic worldview. This research paper reviews that the existence of such codes allows to explain the emergence of stereotypes which reflect experience and knowledge of the given culture bearer which in turn influences the appearance of language universals.